Evaluasi Kontribusi Aspal dan Agregat Dalam Mendukung Kekuatan Bahan RAP (Reclaimed Asphalt Pavement) - Pramindana, Mada, Ir. Sri Sunarjono, MT, Ph.D, Ika Setiyaningsih, ST, MT (2016)
RAP (Reclaimed Asphlat Pavement) consists of degraded aggregate and aged bitumen. The quality of RAP mixture don't still competitive when compared with hot mix. Because this decreasing quality (physical properties and mechanical strength) from RAP, but RAP still have quality and can be used as recycle materials. With that indications then need to evaluate the contribution of aged bitumen and aggregate ini supporting the strength of RAP. This research using RAP from Tegal in northern coast line. This research didn't use any added ingredients. The first this RAP to checks identity among other color, asphalt content, moisture content. Researchers doing to checks that orientation aggregate, physical properties, and mechanical strength. After that RAP to extracted, then aggregate RAP will be checks again as in the check of RAP. After checking in the laboratory, and then the data is calculated and analyzed from each type of examination. Then it can be seen whether that contribute in to build strength of the RAP. Following the results of the examination. The results test identity of RAP that color is bromn grayish, because RAP is materials aged. Proven also with asphalt content is also relatively low at 4,16%. The results test of orientation aggregate showed that asphalt and cluster that blanketed the surface of the aggregate inhibit aggregate moves to fill the void. The test results pf sieve analysis gradation of the RAP tend to be more rugged than the specification of AC-BC and aggregate of RAP. Test of spesific gravity and absorption to available the value of RAP is lower than the aggregate of RAP. Test of flakiness and elongation index to available the aggregate from RAP is already changing its of the shape. Test sand equivalent obtained value of SE from RAP is higher than aggregate of RAP. Test density obtained value of bulk density from aggregate RAP is higher than RAP. The results test of mechanical strength obtained the aggregate RAP is aging so easily obsolescent to exposed load and chemical liquid. In other words, asphalt and cluster that blanketed the aggregate this surface to help reduce the load. Based on the evaluation it can be said that the contribution in support of the power of RAP is asphalt and aggregate to work together.